Analisis Pengaruh Likuiditas, Solvabilitas Dan Profitabilitas Terhadap Kebijakan Dividen (Studi Pada Perusahaan Manufaktur Yang Terdaftar di BEI Yang Masuk Dalam Indeks LQ45 Tahun 2013-2017) - Ely Rosalina Munthe (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Ely rosalina munthe, program for business administration studies school of social and political sciences, Mulawaran University. Thesis title analyzes liquidity impact, solvency, and profitability against the dividends (listed in BEI in the lQ45 index 2013-2017), is led by Dr. Finnah fourqonite, s. SOS. , M.si and Mr umar hi salim, SE. , M.M  as my counselor . Policies have to do with the use of profits that are right for shareholders. Essentially, that profit can be divided as dividends or retained to reinvest. The purpose of this composition is to know and to provide empirical proof of liquidity ratios, solvability and profitability against a strong determination of the amount of dividends Shared with shareholders. The population used in this study is manufacturing companies listed at the Indonesian stock exchange and logged in the lQ45 index from 2013-2017. The method used in sample collection is using tangible sampling, with a total of 7 companies being designated as samples. The analysis that works in this research is regression analysis. The results of this study indicate that liquidity and solvency have no effect on dividend policy, while the profitability variable has a significant influence on dividend policy. The results of the coefficient of determination show that 27.1% of the Dividend Policy is influenced by Liquidity, Solvency and Profitability, while the remaining 72.9% is influenced by other factors. This is important as a consideration of the company's financial management in taking dividend distribution policies and helping investors as information and consideration before investing.